Reinterpreting the “times of crisis” based on the asymmetry between chronos and kairos - Ramalho, Walderez (História da Historiografia: International Journal of Theory and History of Historiography, 2021)
In this article, I argue that the concept of crisis entails a particular form of experiencing and thinking historical time that can only be properly grasped by considering the asymmetry between chronos and kairos. After exploring the main meanings of these two Greek terms for “time”, I show that the chronos paradigm holds hegemony in contemporary theorizations on historical time. Reinhart Koselleck, who construed an influential conceptual history of “crisis”, reiterated such hegemony in his interpretation of the concept’s temporal sense by associating it with the phenomenon of temporal acceleration. This article argues that Koselleck’s interpretation is insufficient since “crisis” encompasses certain dimensions of temporal experience that can only be understood through the notion of kairos – namely, the temporality of decision, urgency, imminent rupture, and uncertainty about the future.